INJEKSI INTRAVITREAL RANIBIZUMAB PADA POLYPOIDAL CHOROIDAL VASCULOPATHY (PCV) - Haris Budiman; Weni Helvinda (Universitas Fort De Kock, 2020)
Introduction: Polypoidal choroidal vasculopathy (PCV) is a peculiar form of choroidal neovascularization characterized by protrusion of the aneurysm at the end of the choroidal blood vessels. The aim of this study is to report a case of PCV in a young woman who treated with intravitreal ranibizumab injection. Method: The patient undergoes general ophthalmic examinations, amsler grid, funduscopic photography and OCT analysis. The repeated examination performed after intravitreal injection of ranibizumab to assess the effect of therapy. Result: Two weeks after intravitreal ranibizumab injection, the visual acuity was improved and on OCT examination revealed decreasing in macular thickness. Conclusion: Intravitreal ranibizumab injection can give good result, but in this case the effectiveness hasn’t so evident because of the administration only once and follow-up only in two weeks.